Stereotactic Body Radiotherapy as Treatment for Organ Confined Low- and Intermediate-Risk Prostate Carcinoma, a 7-Year Study - Katz, Alan Jay; Kang, Josephine (Frontiers in Oncology, 2014)
Objectives: Stereotactic body radiation therapy (SBRT) takes advantage of the prostate’s low α/β ratio to deliver a large radiation dose in few fractions. Initial studies on small groups of low-risk patients support SBRT’s potential for clinical efficacy while limiting treatment-related morbidity and maintained quality of life (QOL). This prospective study expands upon prior studies to further evaluate SBRT efficacy for a large patient population with organ confined, low- and intermediate-risk prostate cancer patients. Methods: 477 patients with prostate cancer received CyberKnife SBRT. The median age was 68.6 years and the median PSA was 5.3 ng/ml. 324 patients were low-risk (PSA < 10 ng/ml and Gleason < 7), 153 were intermediate-risk (PSA 10-20 ng/ml or Gleason = 7). Androgen deprivation therapy was administered to 51 patients for up to six months. 154 patients received 35 Gy delivered in 5 daily fractions; the remaining patients received a total dose of 36.25 Gy in 5 daily fractions. Biochemical failure was assessed using the Phoenix criterion. Results: Median follow up was 72 months. The median PSA at 7 years was 0.11 ng/ml. Biochemical failures occurred for 11 low-risk patients (2 locally), 14 intermediate-risk patients (3 locally). The actuarial 7-year freedom from biochemical failure was 95.6% and 89.6% for low- and intermediate-risk groups, respectively (p < 0.012). Among patients with intermediate-risk disease, those considered to have low intermediate-risk (Gleason 6 with PSA>10, or Gleason 3+4 with PSA <10; n=106) had a significantly higher bDFS than patients with high intermediate-risk (Gleason 3+4 with PSA 10-20 or Gleason 4+3; n=47), with bDFS of 93.5% versus 79.3%, respectively. For the low and low intermediate-risk groups, there was no difference in median PSA nadir or biochemical disease control between doses of 35 and 36.25 Gy. Conclusions: CyberKnife SBRT produces excellent biochemical control rates. Median PSA levels compare f